A Cationic Stearamide-based Solid Lipid Nanoparticle for Delivering Yamanaka Factors: Evaluation of the Transfection Efficiency - Alkan, Funda; Varli, Hanife Sevgi; Demirbilek, Murat; Kaplan, Engin; Lacin, Nelisa Turkoglu (WILEY-V C H VERLAG GMBH, 2020)
Induced pluripotent stem cells (IPSC) are preferred as an alternative source for regenerative medicine, disease modeling, and drug screening due to their unique properties. As seen from the previous studies in the literature, most of the vector systems to transfer reprogramming factors are viral-based and have some well-known limitations. This study aims to develop a non-viral vector system for the transfection of reprogramming factors. Cationic stearamide lipid nanoparticles (CSLN) were prepared via the solvent diffusion method. The obtained CSLNs were used for the delivery of plasmid DNA (pDNA) encoding Oct3/4, Sox2, Klf4, and GFP to fibroblast cell lines. The optimization studies, for zeta potential and particle size of the conjugate, was performed to achieve high cell viability. CSLN63 with 36.5 +/- 0.06 mV zeta potential and 173.6 +/- 13.91 nm size was used for the transfection of Fibroblast cells. The transfection efficiency was observed by following GFP expression and was found as 70 %+/- 0.11. The expression of the Oct4, Sox2, Klf4 was determined by RT-qPCR; an increase was observed after the 12th cycle in Klf4 (Ct averages: 13,41), Sox2 (Ct averages; 12,4), Oct4 (Ct average; 13,77). The tendency of colonization was observed. The upregulation efficiency of Oct4 and SSEA-1 with CSLN and another non-viral vector designed for the transportation of Yamanaka factors developed in our lab previously were compared with flow cytometer analysis.
Keywords: cationic nanoparticle; fibroblast; induced pluripotent stem cell; reprogramming factors; stearamide; PLURIPOTENT STEM-CELLS; NONVIRAL VECTORS; GENE-TRANSFER; VIRAL VECTORS; CO-DELIVERY; DNA; THERAPY; CYTOTOXICITY; GENERATION; POLYMERS; Chemistry